Narrative review of the control and prevention of knowlesi malaria - Mohammad, Ahmad Hazim; Naserrudin, Nurul Athirah; Abdul Rahim, Syed Sharizman Syed; Jelip, Jenarun; Atil, Azman; Sazali, Mohd Fazeli; Muyou, Adora J.; Kunasagran, Priya Dharishini; Ahmad Kamarudin, Nornazirah; Azhar, Zahir Izuan; Dapari, Rahmat; Jeffree, Mohammad Saffree; et al. (Multidisciplinary Digital Publishing Institute, 2022)
Despite the reduction in the number of cases of human malaria throughout the world, the incidence rate of knowlesi malaria is continuing to rise, especially in Southeast Asia. The conventional strategies for the prevention and control of human malaria can provide some protection against knowlesi malaria. Despite the numerous studies on the risk factors and the innovative methods that may be used to prevent and control the vectors of Plasmodium knowlesi, the incidence rate remains high. An integrated approach that includes environmental intervention should be adopted in order to ensure the successful control of zoonotic malaria. A combination of personal-level protection, vector control and environmental control may mitigate the risk of Plasmodium knowlesi transmission from macaques to humans and, ultimately, reduce the incidence rate of knowlesi malaria.